Microbiology of Infected Walled-off Necrosis Following Severe Acute Pancreatitis. (4th October 2017) - Chihara, Shingo; Sahar, Nadav; Kozarek, Richard; Gluck, Michael
Abstract: Background: Formation of fluid collection occur in about 15–20% following severe acute pancreatitis. These fluid collections could become infected with bacterial and fungal organisms and form infected walled-off necrosis (WON). Management options for WON have evolved over the last decade from invasive surgical intervention to combined percutaneous and endoscopic approach (dual modality drainage (DMD). We describe the culture result of WON obtained with DMD. Methods: The study was performed at Virginia Mason Medical Center, a tertiary medical center located in Seattle. We used a prospective, institutional review board-approved database which include onset of pancreatitis, size of WON, timing of drainage, duration of drain, culture result, antibiotics given, and patient information (gender, age and BMI). The data from December 2007 to December 2016 were analyzed. SAS was used for analysis. Results: A total of 182 patients underwent DMD for symptomatic and infected walled off necrosis of which 76 grew organism with culture. Forty-two were monomicrobial while 34 were polymicrobial. For the monomicrobial isolates, coagulase negative staphylococcus was isolated most frequently (6), followed by Staphylococcus aureus (4) and viridans streptococcus (3). WON was significantly more likely to be seen in older patients ( P = 0.008) and in obese patients ( P = 0.06). The longest diameter of WON nor sex of the patient did not significantly factor into whether the culture grew no organism, one organism, or multiple organisms. Conclusion: This is the largest data evaluating microbiology of infected walled off necrosis. Organisms isolated are mostly colonizers of skin and gastrointestinal tract. Positive cultures were seen more in obese and elder patients. Clinical correlation is needed when deciding whether to treat these organisms or not. Disclosures: R. Kozarek, Boston Scientific: Investigator, Research support